2011
DOI: 10.3892/or.2011.1502
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin provides a therapeutic option through inhibition of mTOR signaling in chronic myelogenous leukemia

Abstract: Abstract. Chronic myelogenous leukemia (CML) is a neoplasm of myeloid progenitor cells expressing Bcr-Abl fusion protein.However, some patients with CML are less likely to respond to imatinib, the inhibitor of Bcr-Abl kinase. Recent studies showed that mTOR pathway can increase responses to imatinib. The analysis of mTOR pathway in CML may provide new insights into possible targets of novel therapies. Therefore, we examined the expression of mTOR pathway molecules in bone marrow cells from CML patients and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…It has recently been shown that the rapamycin-induced mTOR inhibition decreased the proliferation of K562 cell lines. 25 Moreover, clinical and preclinical studies have demonstrated that mTORC1 inhibitors synergized with imatinib to increase apoptosis in CML cells 26 , 27 and restored the sensitivity to imatinib-resistant cells. 14 …”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the rapamycin-induced mTOR inhibition decreased the proliferation of K562 cell lines. 25 Moreover, clinical and preclinical studies have demonstrated that mTORC1 inhibitors synergized with imatinib to increase apoptosis in CML cells 26 , 27 and restored the sensitivity to imatinib-resistant cells. 14 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mTOR pathway has been found to be activated in leukemia cells, especially in cell lines expressing Bcr/Abl (811). Previous studies demonstrated that the mTOR pathway was activated in myeloid leukemia, including CML, and mTOR inhibitor (rapamycin, sapanisertib) could arrest cells at the G 0 /G 1 phase and increase apoptosis in leukemia cells (1214). mTOR is a serine/threonine kinase which plays important roles in the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Protein Kinase B (AKT)/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This is important for mitogen-induced cell proliferation and chemotherapeutic drug resistance in cancer cells (21,22). The authors' previous study showed that p70S6K and 4E-BP1 were overexpressed and phosphorylated in CML bone marrow and K562 cells (12). It was therefore speculated that rapamycin could enhance the antitumor effects of chemotherapy on leukemia cells through downregulating mTOR signaling.…”
Section: Introductionmentioning
confidence: 99%
“…mTOR exists as two functional multi-protein complexes, mTORC1 and mTORC2. Previous studies suggest that inhibition of mTOR phosphorylation by mTOR inhibitors results in inhibition of cell growth, G0/G1 phase arrest, and induction of apoptosis [57]. However, the traditional mTOR inhibitors rapamycin and rapalogs, either used as single agent or in combination with other drugs, only have modest clinical activity against various tumors.…”
Section: Introductionmentioning
confidence: 99%